The instantly blocking-based fluorescent immunochromatographic assay for the detection of SARS-CoV-2 neutralizing antibody - Li, Yizhe; He, Jinyong; Zhang, Ying; Liang, Dan; Zhang, Jiaqi; Ji, Ruili; Wu, Yue; Su, Zejie; Ke, Changwen; Xu, Ning; Tang, Yong; Xu, Jianhua (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction At present, there is an urgent need for the rapid and accurate detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) neutralizing antibodies (NAbs) to evaluate the ability of the human body to resist coronavirus disease 2019 (COVID-19) after infection or vaccination. The current gold standard for neutralizing antibody detection is the conventional virus neutralization test (cVNT), which requires live pathogens and biosafety level-3 (BSL-3) laboratories, making it difficult for this method to meet the requirements of large-scale routine detection. Therefore, this study established a time-resolved fluorescence-blocking lateral flow immunochromatographic assay (TRF-BLFIA) that enables accurate, rapid quantification of NAbs in subjects. Methods This assay utilizes the characteristic that SARS-CoV-2 neutralizing antibody can specifically block the binding of the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein and angiotensin-converting enzyme 2 (ACE2) to rapidly detect the content of neutralizing antibody in COVID-19-infected patients and vaccine recipients. Results When 356 samples of vaccine recipients were measured, the coincidence rate between this method and cVNT was 88.76%, which was higher than the coincidence rate of 76.97% between cVNT and a conventional chemiluminescence immunoassay detecting overall binding anti-Spike-IgG. More importantly, this assay does not need to be carried out in BSL-2 or 3 laboratories. Discussion Therefore, this product can detect NAbs in COVID-19 patients and provide a reference for the prognosis and outcome of patients. Simultaneously, it can also be applied to large-scale detection to better meet the needs of neutralizing antibody detection after vaccination, making it an effective tool to evaluate the immunoprotective effect of COVID-19 vaccines.